(untitled) (CIPEEX, 2025)
The research investigates the (in)effectiveness of public urban mobility policies in the Jardim das Oliveiras neighborhood in Senador Canedo, from the perspective of the right to the city as a fundamental human right. The central problem identified is inequality in access to urban mobility, which compromises the dignity of citizens, especially those with disabilities. Current policies have been ineffective in guaranteeing full access to mobility, which results in violations of rights and inadequate accessibility conditions for the most vulnerable population. The general objective of the research is to evaluate the effectiveness of these public policies in the Jardim das Oliveiras neighborhood, with a focus on urban mobility. The specific objectives include: (a) understanding the connections between the right to the city and the Sustainable Development Goals (SDGs), as instruments for promoting fairer and more inclusive cities; (b) analysing Brazilian legislation related to the right to the city, paying special attention to the constitutionalization of urban development policies and the role of the master plan; and (c) carrying out a critical analysis of the urban mobility policies implemented in the neighbourhood, identifying their gaps, challenges and possible opportunities for improvement. The methodology adopted is a mixed approach, combining quantitative and qualitative research. Data collection includes a literature review, document analysis, statistical data collection and the use of geospatial tools to assess urban infrastructure and accessibility in the neighborhood. This methodology allows for a comprehensive analysis of the impacts of public mobility policies on the quality of life of the inhabitants of Jardim das Oliveiras. The justification for the research is based on the need to promote more equitable urban development, especially in peripheral and less favored areas such as Jardim das Oliveiras. By analyzing urban mobility as an essential human right, the study seeks to provide subsidies for the formulation of more inclusive and effective public policies. The results of the research indicate that public urban mobility policies in the neighborhood are insufficient to meet the needs of the population, particularly people with disabilities, who face serious accessibility problems. Inadequate sidewalks and a lack of cycling infrastructure aggravate the situation, limiting access to more sustainable forms of transportation, such as walking or cycling. In addition, the predominance of individual transportation by car or motorcycle, coupled with the lack of efficient public alternatives, reflects the failure to implement intercity mobility solutions for those who depend on commuting to Goiânia. Based on these findings, the research recommends the implementation of inclusive and effective public policies that prioritize improvements in urban infrastructure, accessibility and public transport. The construction of bike lanes, accessible sidewalks and an efficient public transportation network are essential to ensure that all citizens, especially the most vulnerable, can fully exercise their right to the city. These advances are seen as fundamental to promoting a more equitable, accessible and sustainable urban environment.